Molecular Insights into Propylthiouracil as a Thyroid Peroxidase Inhibitor: A Computational Study Approach - Suryandari, Dwi Anita; Yunaini, Luluk; Sunaryo, Hadi; Istiadi, Khaerunissa Anbar; Pratomo, Irandi Putra (UI Scholars Hub, 2024)
Thyroid peroxidase (TPO) is a crucial enzyme in the biosynthesis of thyroid hormones, catalyzing the iodination of tyrosine residues in thyroglobulin and the coupling of iodotyrosines to form thyroxine (T4) and triiodothyronine (T3). Propylthiouracil (PTU) is an antithyroid drug commonly used to manage hyperthyroidism by inhibiting TPO. Understanding the molecular interactions between TPO and PTU can provide insights into the inhibitory mechanisms and guide the design of more effective antithyroid medications. Objective: This study aims to elucidate the binding interactions between TPO and PTU through molecular docking, providing a detailed understanding of how PTU inhibits TPO activity. Methods: The three-dimensional structure of TPO was obtained from Prosite and modelling by swissmodel and prepared for docking. The structure of PTU was optimized, and molecular docking was performed using AutoDock. The binding affinity, binding poses, and key interactions between TPO and PTU were analyzed. Visualization of the docking results was performed using PyMOL to identify critical residues involved in PTU binding. Results: The docking analysis revealed that PTU binds effectively to the active site of TPO with a binding affinity of -5.45 kcal/mol. The interaction involves coordination with the heme group and several key residues, including His239, which coordinates the heme, and Ser314, which forms hydrogen bonds with PTU. Additionally, hydrophobic interactions with residues Phe241 and Ile399 stabilize the binding of PTU in the active site. Conclusion: The docking study highlights the significant interactions between PTU and TPO, elucidating the molecular basis of TPO inhibition by PTU. The binding affinity and key interactions identified in this study provide a foundation for the design of more potent antithyroid drugs.